Argumentation, the study of effective reasoning - Zarefsky, David; Teaching Company (Chantilly, VA Teaching Co., 2001)
Dr. David Zarefsky, professor of communication studies at Northwestern University, delivers lectures covering the history of rhetoric and debate as well as analysis of different types of arguments in various situations.
Lecture 1. Introducing argumentation and rhetoric -- Lecture 2. History of argumentation studies -- Lecture 3. Formal and informal argument -- Lecture 4. The emergence of controversy -- Lecture 5. Resolutions and issues -- Lecture 6. Stasis, the focal point of dispute -- Lecture 7. Presumption and burden of proof -- Lecture 8. Argument analysis and diagramming -- Lecture 9. Claims and evidence -- Lecture 10. Reasoning from parts to whole -- Lecture 11. Moving from cause to effect -- Lecture 12. Establishing correlations -- Lecture 13. Analogy, narrative and form -- Lecture 14. What makes a sound argument? -- Lecture 15. Fallacies in reasoning -- Lecture 16. Validity and fallacies reconsidered -- Lecture 17. Assembling a case -- Lecture 18. Attack and defense I -- Lecture 19. Attack and defense II -- Lecture 20. Language and style in argumentation -- Lecture 21. Arguments between friends -- Lecture 22. Arguments among experts -- Lecture 23. Public argument and democratic life -- Lecture 24. The ends of argumentation.
Teaching Co.: 497--498.
In two containers (23 cm.).
Keywords: Debates and debating; Forensics (Public speaking); Reasoning; Rhetoric